Review of training & development policy, compensation & benefit, health & safety of berger paints Bangladesh Ltd. (Chittagong factory) - Chowdhury, Marjana Mahjabin (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.